Traffic accidents, maxillofacial injuries and risk factors: A systematic review of observational studies. Issue 1 (2nd December 2018) - da Nóbrega, Lorena Marques; de Macedo Bernardino, Ítalo; Leal, Paula Miliana; de Castro Martins, Carolina; Granville‐Garcia, Ana Flávia; d'Avila, Sérgio
Abstract: Aim: This study aimed to evaluate the scientific evidence regarding the risk factors for maxillofacial injuries among victims of traffic accidents. Method: A systematic review of articles published until February 2017 was carried out in the following databases: PubMed, Web of Science, Scopus, and Cochrane Library. Studies were selected by two independent reviewers (ϰ = 0.841). The risk of bias in the selected studies was assessed using an adapted version of the Newcastle‐Ottawa Scale for observational studies. Results: A total of 2703 records were found, of which only three articles fulfilled the inclusion criteria and were analyzed, including 422 244 patients. The male/female ratio ranged from 3.4: 1 to 6: 1. All eligible studies performed the multivariate statistical analysis. Eleven risk factors for maxillofacial traumas were identified: victim's gender ( P  < 0.05), age group (P < 0.05), residence region (P < 0.05), impact characteristics ( P  < 0.05), increased net change in velocity due to collision ( P  < 0.05), increase in occupant's height ( P  < 0.05), nonuse of protective equipment ( P  < 0.05), type of accident ( P  < 0.05), time of occurrence ( P  < 0.05), lesion severity ( P  < 0.05), and occurrence of concomitant lesions ( P  < 0.05). Conclusion: The results suggest that sociodemographic characteristics, as well as those related to the collision patterns and circumstances of traffic accidents, may influence the occurrence of maxillofacial injuries. However, the results should be interpreted with caution due to the high heterogeneity among studies.